PERAN GAYA KEPEMIMPINAN DALAM PENINGKATAN KINERJA KARYAWAN DI KAWASAN ASIA TENGGARA - Municha, Eka Sufistika; Nurhaliza, Herlina; Ratnawati, Arina Iski (ITB Swadharma, 2024)
Leadership style was a crucial aspect of organizational dynamics that influenced interactions between leaders and their subordinates. To achieve optimal employee performance, it was necessary to apply an effective leadership style. This study aimed to determine the comparison of leadership styles in the Southeast Asia region and their role in improving employee performance. The method used was a literature study of various relevant previous literature and empirical research within the last ten years (2015-2024), using ScienceDirect, Google Scholar, and Semantic Scholar. The study results show that leadership style has a positive influence and significant impact on improving employee performance in the Southeast Asia region. More specifically, transformational and democratic styles have the most significant positive influence in Indonesia, Malaysia, Cambodia, Timor Leste, and the Philippines, especially in terms of employee motivation and participation. Meanwhile, laissez-faire and transactional leadership styles have the most significant positive influence in Vietnam, especially in terms of employee complete freedom and orientation to rulesGaya kepemimpinan merupakan aspek krusial dalam dinamika organisasi yang memengaruhi interaksi antara pemimpin dan bawahannya. Untuk mencapai kinerja karyawan yang optimal, maka perlu diterapkan gaya kepemimpinan yang efektif. Studi ini bertujuan untuk mengetahui perbandingan gaya kepemimpinan di kawasan Asia Tenggara dan perannya dalam peningkatan kinerja karyawan. Metode yang digunakan adalah studi kepustakaan dari berbagai literatur dan penelitian empiris terdahulu yang relevan dalam rentang waktu sepuluh tahun terakhir (2015-2024), dengan menggunakan ScienceDirect, Google Scholar, dan Semantic Scholar. Hasil studi menunjukkan bahwa gaya kepemimpinan mempunyai pengaruh positif dan dampak yang signifikan dalam meningkatkan kinerja karyawan di kawasan Asia Tenggara. Secara lebih spesifik, gaya transformasional dan demokrasi memiliki pengaruh positif yang paling signifikan di negara Indonesia, Malaysia, Kamboja, Timor Leste, dan Filipina, terutama dalam hal motivasi dan partisipasi karyawan. Sementara gaya kepemimpinan laissez-faire dan transaksional memiliki pengaruh positif yang paling signifikan di negara Vietnam, terutama dalam hal kebebasan penuh karyawan dan orientasi pada aturan